Clinical Features of Female Carriers and Prodromal Male Patients With Spinal and Bulbar Muscular Atrophy. (3rd January 2023) - Torii, Ryota; Hashizume, Atsushi; Yamada, Shinichiro; Ito, Daisuke; Kishimoto, Yoshiyuki; Moriyoshi, Hideyuki; Inagaki, Tomonori; Nakamura, Ryoichi; Nakamura, Tomohiko; Naoi, Tameto; Morita, Mitsuya; Katsuno, Masahisa
Abstract : Background and Objectives: To assess the clinical and electrophysiologic features of female carriers and early-stage male patients with spinal and bulbar muscular atrophy (SBMA) to elucidate the early pathophysiologic changes of the disease. Methods: Female carriers, early-stage male patients with SBMA, and age-matched male and female healthy controls were recruited. The results of motor functional scales, motor unit number estimation, dual-energy X-ray absorptiometry, and peripheral blood tests were compared between female carriers and healthy female controls and between patients with SBMA and healthy male controls. EMG was also investigated in female carriers. Results: We enrolled 21 female carriers and 11 early-stage male patients. Seventeen female and 14 male age-matched healthy controls were also enrolled. Female carriers experienced early-stage symptoms such as muscle cramps more frequently than healthy female controls. Decreased motor unit number estimation and EMG abnormalities including high amplitude or polyphasic potentials were observed in female carriers together with mild muscle weakness in neck flexion and a slow walking speed. Changes of muscle-related markers, including serum creatine kinase and dual-energy X-ray absorptiometry, were clearly detected in early-stage male patients with SBMA, but not in female carriers. Discussion: The present study revealed that female carriers of SBMA manifest mild muscular weakness associated with changes in neurogenic biomarkers. Conversely, male patients showed neurogenic and myopathic changes even at the early stage. These results suggest a testosterone-independent neurodegenerative pathophysiology in female SBMA carriers.